Influence of organic manures on soil nutrient content, microbial population, yield and quality parameters of pomegranate (Punica granatum L.) cv. Bhagwa - Ramesh Chand Choudhary (PLoS ONE, 2022)
During the last era in India, the use of chemical fertilizer has increased tremendously. The excessive use of these chemicals leads to the degradation of soil quality, health, as well as nutritional status. These are also causing a degradation of human health. This experiment was conducted during Mrig Bahar (July to December) during two consecutive years (2019–2020)in a randomized block design with three replications in which six-year-old 42 pomegranate plants were tested with 14 treatments of different organic manures. Findings showed that in the various treatments, the organic combination T13-Jeevamrut 16.08 L plant-1 + Vermicompost 24.79 kg plant-1 had a significant effect on the nutritional status (available nitrogen, available phosphorus, and available potassium) and microbial population (fungi, bacterial, and actinomycetes count). In addition, T13-Jeevamrut 16.08 L plant-1 + Vermicompost 24.79 kg plant-1 found a significant effect on fruit yield characteristics like fruit plant-1 (122.00), fruit yield (17.38 kg plant-1), fruit weight (192.50 g) and fruit quality characteristics such as fruit juice percent (52.92%), and total sugar (11.92%).